A securitização dos Clubes de Motociclistas: estudo de caso do Hells Angels Motorcycle Club no Canadá - Cardoso, Paula Venancio (2024)
This dissertation proposes an in-depth investigation into the historical evolution and contemporary perception of motorcycle clubs, with a particular emphasis on outlaw clubs, from their origins to the present day. The research adopts a qualitative approach, combining a thorough review of existing literature with a detailed analysis of data to provide a comprehensive understanding of the role of these clubs in society. Throughout the text, various aspects are explored, including the formation and consolidation of motorcycle clubs, their relationship with transnational organized crime, and the narrative construction portraying them as a threat to public security. A specific focus is given to the case study of the Hells Angels Motorcycle Club (HAMC) in Canada, recognized as one of the most emblematic organizations in the country. Furthermore, through critical examination, the research addresses gaps in the field, particularly regarding the characterization of clubs as criminals organizations and the varying levels of their involvement in illegal activities. Finally, the strategies adopted by authorities to deal with these groups are discussed, highlighting the application of securitization theory as a lens for understanding policies related to outlaw motorcycle clubs. In conclusion, the dissertation aims to contribute to future research on One Percent clubs and their classification as criminal organizations, emphasizing the need for further studies on the formation of clubs, their transnational dynamics, and the impact of securitized countermeasures on these organizations